The significance of seasonal light and temperature interaction for the latitudinal distribution of seaweeds: biochemical and physiological raw data of a long-term multi-factorial experiment - Nora Diehl; Philipp Laeseke; Inka Bartsch; Margot Bligh; Hagen Buck-Wiese; Jan-Hendrik Hehemann; Sarina Niedzwiedz; Niklas Plag; Ulf Karsten; Tifeng Shan; Kai Bischof (PANGAEA, 2024)
Due to the global rise in temperature, recent studies predict species shifts towards higher latitudes. The temperate kelp Laminaria hyperborea (Phaeophyceae) is an abundant European bioengineering species that is widely distributed between northern Portugal and northern Norway, however not yet found in the High Arctic. To investigate its ability of the species to invade the high latitudes under past, present and future temperature scenarios, we conducted a long-term multi-factorial experiment using tissue of adult sporophytes of L. hyperborea collected from Porsangerfjorden, Norway. The samples were exposed to three different photoperiods (PolarNight, PolarDay, LongDay) at 0, 5 and 10°C for three months. The maximum photosynthetic quantum yield of photosystem II (Fv/Fm; Imaging-PAM, Walz GmbH Mess- und Regeltechnik, Effeltrich, Germany) was monitored once a week. For monitoring of potential growth, the size of the algal discs was photographed every two weeks and analyzed with ImageJ (Version 1.52a). Every four weeks, subsamples for monitoring the dry weight and for the biochemical analyses were taken. Laminarin content was determined following via enzymatic digestion. Mannitol concentration was analyzed using a HPLC. Phlorotannins were analyzed following the photometric Folin-Ciocalteu method. Absolut pigment concentrations were also analyzed using a HPLC and pool sizes, the de-epoxidation state of the xanthophyll cycle (DPS), and the ratios calculated afterwards.